Characterization of MSlys, the endolysin of Streptococcus pneumoniaephage MS1 - Silva, Maria Daniela (2020)
Despite the use of pneumococcal conjugate vaccines, the number of infections related to Streptococcus pneumoniae continues to be alarming. Herein, we identified, characterized the MSlys endolysin encoded in the phage MS1. We further tested its antimicrobial efficacy against planktonic and biofilm cells, assessing the culturability of cells and biofilm structure by scanning electron microscopy, and confocal laser scanning microscopy. The modular MSlys endolysin consists of an amidase catalytic domain and a choline-binding domain. MSlys is active against isolates of children with otitis media, and conditions close to those found in the middle ear. Treatment with MSlys (2h, 4 µM) reduced planktonic cultures by 3.5 log10 CFU/mL, and 24- and 48-h-old biofilms by 1.5 and 1.8 log10 CFU/mL, respectively. Imaging of the biofilms showed thinner and damaged structures compared to control samples. The recombinantly expressed MSlys may be a suitable candidate for treating pneumococcal infections, including otitis media.